Palliative care after stroke: A review. Issue 6 (August 2021) - Cowey, Eileen; Schichtel, Markus; Cheyne, Joshua D; Tweedie, Lorna; Lehman, Richard; Melifonwu, Rita; Mead, Gillian E
Background: Palliative care is an integral aspect of stroke unit care. In 2016, the American Stroke Association published a policy statement on palliative care and stroke. Since then there has been an expansion in the literature on palliative care and stroke. Aim: Our aim was to narratively review research on palliative care and stroke, published since 2015. Results: The literature fell into three broad categories: (a) scope and scale of palliative care needs, (b) organization of palliative care for stroke, and (c) shared decision making. Most literature was observational. There was a lack of evidence about interventions that address specific palliative symptoms or improve shared decision making. Racial disparities exist in access to palliative care after stroke. There was a dearth of literature from low- and middle-income countries. Conclusion: We recommend further research, especially in low- and middle-income countries, including research to explore why racial disparities in access to palliative care exist. Randomized trials are needed to address specific palliative care needs after stroke and to understand how best to facilitate shared decision making.